Half-marathon running performance is not improved by a rate of fluid intake above that dictated by thirst sensation in trained distance runners - Dion, T.; Savoie, F. A.; Asselin, A.; Gariepy, G.; Goulet, E. D. B. (European Journal of Applied Physiology, 2013)
Purpose It has been demonstrated that exercise-induced dehydration (EID) does not impair, and ad libitum drinking optimizes, cycling time-trial (TT) performance. However, the idea that EID > 2 % bodyweight (BW) impairs endurance performance is well ingrained. No study has tested the impact of EID upon running TT performance. We compared the effects of thirst-driven (TD) vs. programmed fluid intake (PFI) aimed at maintaining EID-associated BW loss <2 % on half-marathon performance. Methods Ten trained distance runners underwent, in a randomized, crossover fashion, two, 21.1 km running TTs on a treadmill (30 °C, 42 % relative humidity) while facing a wind speed matching running speed and drinking water (1) according to thirst sensation (TD) or (2) to maintain BW loss <2 % of their pre-exercise BW (PFI), as recommended by the American College of Sports Medicine. Results Despite that PFI significantly reduced EID from 3.1 ± 0.6 (TD) to 1.3 ± 0.7 % BW (PFI), mean rectal temperature from 39.4 ± 0.4 to 39.1 ± 0.3 °C, mean body temperature from 38.1 ± 0.4 to 37.7 ± 0.2 °C and mean heart rate from 175 ± 9 to 171 ± 8 bpm, neither half-marathon time (TD 89.8 ± 7.7; PFI 89.6 ± 7.7 min) nor running pace (TD 4.3 ± 0.4; PFI 4.2 ± 0.4 min/km) differed significantly between trials. Conclusion Albeit providing trivial cardiovascular and thermoregulatory advantages, in trained distance runners, PFI (1,380 ± 320 mL/h) offers no performance benefits over TD fluid intake (384 ± 180 mL/h) during a half-marathon raced under warm conditions.